2014
DOI: 10.1007/s11664-014-3489-3
|View full text |Cite
|
Sign up to set email alerts
|

Junction and Back Contact Properties of Spray-Deposited M/SnS/In2S3/SnO2:F/Glass (M = Cu, Graphite) Devices: Considerations to Improve Photovoltaic Performance

Abstract: SnS/In 2 S 3 heterojunction devices were fabricated entirely by chemical spray pyrolysis in a superstrate configuration on SnO 2 :F/glass. The SnS/In 2 S 3 junction was found to exhibit strong rectification behavior, and the MottSchottky characteristics showed it was abrupt. The photovoltaic behavior of the junction was investigated under air mass 1.5G illumination, showing a short-circuit current of 4.8 mA/cm 2 and an open-circuit voltage of 0.29 V, reportedly the highest to date among similar devices with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…The unit cell dimensions of orthorhombic structure, a, b and c values were evaluated using (101), ( 011) and (111) planes by following the Fig. 2 The GIXRD patterns of SnS 1−x Se x thin films prepared at different substrate temperatures relation (2). The unit cell volume (V) of the films was calculated using relation (3).…”
Section: Structural Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The unit cell dimensions of orthorhombic structure, a, b and c values were evaluated using (101), ( 011) and (111) planes by following the Fig. 2 The GIXRD patterns of SnS 1−x Se x thin films prepared at different substrate temperatures relation (2). The unit cell volume (V) of the films was calculated using relation (3).…”
Section: Structural Propertiesmentioning
confidence: 99%
“…Among them, SnS and SnSe are promising light absorbing materials used for low cost thin film solar cell applications owing to their earth abundance, less toxicity of constituent elements and favourable physical properties. Both these materials showed high optical absorption coefficient (~ 10 5 cm −1 ) and tunable optical band gap energy (1-2 eV) [1][2][3][4][5][6]. Moreover, both SnS and SnSe are p-type semiconductors exhibiting orthorhombic crystal structure with optical band gaps of 1.3 eV and 1.0 eV respectively [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…[96a, 97] The carboxylsilanes can be easily prepared from vinyltrichlorosilane and the corresponding acids such as lauric acid, myristica cid, and caprylic acid, etc. [97] Interestingly,t he silylatedd erivatives from these acid catalysts such as silyl phosphate compounds [93c, 98] and silyl carboxylic acids (24, 25,S cheme 22) [99] have attracted particulari nterest because the silylation may improve the compatibilitya nd dispersibility of catalysts in the compositions, especially for the inorganic acid catalysts. It is found that compositions employing silylated carboxylic acids in combination with certain adhesion promoters (amino-containing silane/siloxane compounds, e.g., g-aminopropyltriethoxysilane)exhibits good curing behavior,s imilar to or even bettert han organotin compounds, indicating that these materials are suitable as replacementsf or organotino ro ther metal-based catalysts in the manufacture of RTV silicone elastomers.…”
Section: Metal-free Systemsmentioning
confidence: 99%
“…It is found that compositions employing silylated carboxylic acids in combination with certain adhesion promoters (amino-containing silane/siloxane compounds, e.g., g-aminopropyltriethoxysilane)exhibits good curing behavior,s imilar to or even bettert han organotin compounds, indicating that these materials are suitable as replacementsf or organotino ro ther metal-based catalysts in the manufacture of RTV silicone elastomers. [99] The silyl group can be directly bonded to the carboxylic acid, or through ah ydroxyl group on the carboxylic acid. Moreover,t he amount of these catalysts can not only affect the rate of the surfacec ure time and the bulk or complete cure time, buta lso the viscosity of the composition.…”
Section: Metal-free Systemsmentioning
confidence: 99%
See 1 more Smart Citation